PV/Wind Hybrid Energy System, Modeling and Simulation at variable weather conditions - Abdelhamid Slama; Messaoud Hamouda; Mounir Khiat (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This paper presents a modeling and simulation of a grid-connected wind / PV hybrid power system under variable weather conditions. This system includes a wind turbine system, a PV system that shares a DC bus, and no battery. The paper contains an overview of the hybrid system and some previous studies; it presents a brief overview of each component used for this system. Signal distortion remains the great obstacle when connecting to the grid, so the system architecture and its proposed control are also introduced to reduce the distortion of electrical signals to an acceptable value. A simulation of the system’s operation with specific weather conditions in three different modes was performed using the MATLAB Simulink to describe the effect of these weather conditions on the production of electrical energy. Simulation results show how these weather conditions affect the operation of this hybrid system. An acceptable distortion value of the produced current signals has also been reached. These results present an evaluation of the dynamic performance of this system under the proposed working conditions. It also shows the energy exchange with the grid.